Analisis Dampak Penataan Kawasan Batang Agam terhadap Kesejahteraan Masyarakat Lokal - Ash-shiddiqie, Muhammad Irsyad; Andrianus, Fery (Jurnal Informatika Ekonomi Bisnis, 2025)
This study analyses the impact of the Batang Agam area arrangement on the welfare of local communities in Payakumbuh City, West Sumatra, focusing on three main variables: area zoning regulations, infrastructure and environment. Through a quantitative approach with logistic regression method, data was collected from 106 businesses around the Batang Agam area. The results showed that environmental quality has a significant influence on increasing community income, with an odds ratio of 21,300.88. This indicates that a clean, safe and well-managed environment is a major factor in driving economic activity. In contrast, zoning regulations and infrastructure did not show a significant impact, possibly due to their sub-optimal implementation or inappropriate to local needs. These findings underscore the importance of environmental management as a key foundation in zoning, while emphasising the need to re-evaluate zoning and infrastructure policies to be more responsive to community needs. The research also highlights the importance of community participation in the planning process to ensure that development policies are truly inclusive and sustainable. The implication of these findings is the need for a holistic approach to zoning, which focuses not only on physical aspects, but also on improving the quality of life and well-being of local communities. As such, this research provides valuable input for local governments in designing more effective and sustainable development policies in riverside areas.